2021
DOI: 10.1080/10872981.2021.1913784
|View full text |Cite
|
Sign up to set email alerts
|

Rewarding journeys: exploring medical students’ learning experiences in international electives

Abstract: International electives are recognized as a high-impact practice in clinical education. However, medical students’ actual learning experiences during electives have not been explored fully. Specifically, drawing on language management theory, this exploratory case study investigates students’ perceived learning outcomes and the managing processes by which they gained benefits from cross-cultural learning experiences in international electives. Written reflective reports in a series of e-portfolios were collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 36 publications
(25 reference statements)
0
7
0
Order By: Relevance
“…International clinical placement as part of the ERASMUS exchange program was associated with higher 4-HCS overall scores in our study. Previous studies have suggested that international clinical placement would provide students with the opportunity to develop communication skills [ 41 ]. Yet, the potential for self-selection bias cannot be excluded, reflecting the fact that students with a higher level of communication skills at baseline were selected for international clinical placement and subsequently yielded better communication performance during medical consultations with standardized patients.…”
Section: Discussionmentioning
confidence: 99%
“…International clinical placement as part of the ERASMUS exchange program was associated with higher 4-HCS overall scores in our study. Previous studies have suggested that international clinical placement would provide students with the opportunity to develop communication skills [ 41 ]. Yet, the potential for self-selection bias cannot be excluded, reflecting the fact that students with a higher level of communication skills at baseline were selected for international clinical placement and subsequently yielded better communication performance during medical consultations with standardized patients.…”
Section: Discussionmentioning
confidence: 99%
“…Mota et al argued that the international experience of health professionals is one of the factors associated with accepting migrants [ 36 ]. Although encouraging dentists and dental students in Japan to gain international experience is unrealistic, cultivating a global mindset and cultural competency in undergraduate and clinical education is key to overcoming the challenges of providing treatment and care for migrants [ 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several authors argued that IMEs foster important medical competences, including professional identity formation, interest in humanitarian efforts and volunteerism, and value-based communication as well as personal growth [ 21 23 ]. This may particularly the case with regard to structured electives, which are arranged through reciprocal faculty partnerships or philanthropic sponsorships, and which are characterized by continuous student supervision during the entire elective [ 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%